Nasocardiac reflex during aspiration and injection through a nasogastric tube: An infrequent occurrence - Haldar, Rudrashish (Indian J Crit Care Med, 2015)
Nasocardiac reflex is a relatively less discussed variant of trigeminovagal reflex where the afferent arc of the reflex is represented by any of the branches of the trigeminal nerves, and the efferent arc is via the vagus nerve. Elicitation of this reflex is commonly seen during surgical manipulation and is manifested as bradycardia or even asystole. We report a case where nasocardiac reflex was unusually observed in a patient when aspiration and injection were done through a nasogastric tube.